Daya Dukung Ekowisata Pantai Teluk Penyu Kabupaten Cilacap - Rahmawati, Sofwa Aulia; Sari, Lilik Kartika (Jurnal Ilmu Kelautan Lesser Sunda, 2022)
Ecotourism is tourism based on nature continues to be ecological, social, cultural, and economic to provide an opportunity to appreciate and learn about the elements of the natural environment. Carrying capacity of the area is the maximum number of visitors that physically can be accommodated in the area provided at a specific time without disruption to nature and man. Teluk Penyu Beach in Cilacap is a part of Indonesian ecotourism. In addition to natural scenery, Teluk Penyu Beach has a history, philosophy and hospitality of the people which are the main attraction so that it arouses the curiosity of tourists to visit and explore natural and historical knowledge more deeply. For the development, utilization, and management of the ecotourism potential that exists on the Teluk Penyu Beach, it is necessary to conduct related research on the Analysis of Development and Supporting Capacity of Ecotourism of Teluk Penyu Beach, Cilacap Regency. The purpose of this study is to analyze the efforts that need to be made to develop tourism and to determine the value of the carrying capacity of the Teluk Penyu Coastal Ecotourism Area in Cilacap Regency. The method used in this research is the field survey method. Methods of data collection using observation, documentation, questionnaires or interviews with tourists and managers.